Economic value of the recreational use of Brasília National Park - Ferreira, Alexandre dos Santos (2022)
The environmental valuation is an important tool for the decision making in environmental management but it still needs applications in different contexts, enabling the consolidation of its different methodological approaches. Thus, the present study aimed to estimate the economic value of the recreational use of Brasília National Park in the capital of Brazil, Brasília, and to determine the price-demand elasticity of visitors who are resident in the Federal District. It was used the zonal approach of the travel cost method, for this purpose, questionnaires were applied within the park, from February to March of 2020, in order to obtain information on the travel costs, the number of visits and the socioeconomic data of resident visitors of the Federal District. Then, through regression analysis characteristic of the travel cost method, the economic value of the park is obtained. The economic value of the recreational use of Brasília National Park was BRL 137,667,504.14/year, with a 95% confidence interval between BRL 55,762,205.7 to BRL 219,552,680.9/year. It was found that demand for visits by park visitors residing in the Brazilian capital was elastic due to the zonal approach, an increase in the entrance price negatively affected the well-being of park users, which reduced the frequency of visits and also the recreational value of the park. The relevance of this information demonstrates that there is a potential economic value of direct use of Brasília National Park.